An overview of domestic waste management using the environmental health risk assessment (EHRA) approach in Taman, Sidoarjo - Pratama, Leo Dewa Lucky; Fasya, Abdul Hakim Zakkiy (Universitas Nahdlatul Ulama Surabaya, 2025)
According to the Ministry of Environment and Forestry, in 2020 Sidoarjo Regency ranked 2nd with a total of 390 thousand tons per year. Taman District is the most dense population in Sidoarjo Regency, namely 235,238 people in 2022, divided into 24 villages or sub-districts. This research aims to describe household waste management using the Environmental Health Risk Assessment (EHRA) approach in Taman District, Sidoarjo Regency. This research method is descriptive quantitative using a cross sectional approach. The population of this study were housewives in Taman District, Sidoarjo Regency. The sample for this research was 159 respondents divided into 24 villages or sub-districts. The variables of this research are behavior and habits, environment, reinforcing factors (regulations), enabling factors (facilities). This research instrument uses the EHRA questionnaire. Data analysis in this study used univariate. The research results show that almost all of the regulatory variables (83.6%) do not meet the requirements because there are no regulations for good waste management. Infrastructural variables: almost all (81.8%) have lots of mosquitoes, almost all (85.5%) officers transport rubbish several times a week, and the majority (62.3%) of officers transport rubbish on time. Behavioral and habit variables: the majority (71.7%) collect and throw rubbish into the trash, almost all (86.2%) do not sort the rubbish before throwing it away, the majority (54.5%) do sort the type of glass and glass. Environmental variables: Almost all (91.8%) environmental conditions meet requirements or are clean.